Aesthetic and Spiritual Interpretation of the Father Character in English and Uzbek Literature - Ro‘ziboyeva Maftuna Soyibjon qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
The image of the father in literature reflects important cultural, moral, and emotional values within society. This thesis explores the aesthetic and spiritual interpretation of the father character in English and Uzbek literature. The study uses a comparative approach to analyze how the father is portrayed in different cultural contexts. It focuses on the father’s role as a moral guide, authority figure, and emotional presence. The findings show that Uzbek literature presents the father as a symbol of respect, wisdom, and spiritual strength, while English literature often explores more complex and psychological aspects of fatherhood. The study highlights how literature reflects cultural differences and shared human values.